CORRELATION BETWEEN LEARNING MOTIVATION AND LEARNING ACHIEVEMENT TOWARDS STUDENTS' WORK INTERESTS AT TAMAN SISWA JETIS VOCATIONAL SCHOOL YOGYAKARTA - Ahmad Rofiquddin; Rabiman; Samsul Hadi (Jurusan Pendidikan Teknologi Dan Kejuruan, 2024)
This study aims to examine the relationships between learning motivation, learning achievement in Motorcycle Engine Maintenance, and interest in working in the industrial sector among class XI TBSM students at SMK Tamansiswa Jetis Yogyakarta. Conducted between December 2023 and July 2024, this correlational research used a quantitative approach with a sample of 38 students. The independent variables were learning motivation and learning achievement, while the dependent variable was interest in working in the industrial sector. Data was collected through questionnaires and documentation, and analyzed using SPSS with descriptive analysis, normality tests, linearity tests, multicollinearity tests, and both simple and multiple regression analyses. The results showed: 1) a significant positive relationship between learning motivation and interest in working (p = 0.00, r = 0.69); 2) a significant positive relationship between learning achievement in Motorcycle Engine Maintenance and interest in working (p = 0.00, r = 0.30); and 3) a significant positive relationship between learning motivation, learning achievement, and interest in working (p = 0.00, r = 0.69). It concludes that both learning motivation and achievement significantly influence students’ interest in working in the industrial sector. The study recommends that schools focus on motivating students and researchers explore other factors influencing career interest.